PENGAWETAN KAYU KERUING UNTUK MENARA PENDINGIN (Preservation of keruing woodfor cooling tower) - Barly Barly; Abdurahim Martawijaya; Pipin Permadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
The utiliization of wood for cooling tower in Indonesia tends to increase and has become more important. Wood as material for cooling tower has been applied commercially in several developed countries such as New Zealand,USA and Japan. While in indonesia it has just been started in 1981 after the establishment of Kamojang Geothermal Power Station Unit 1. This paper deals with some experience in treating keruing wood (Dipterocarpus spp.) as material for cooling tower by vacuum-pressure impregnation. The result shows that keruing is easy to treat. In other to meet the retention of 24 kg/m3, the concentration of the solution must be at least 6.25 percent and absortion of 384 liters of preservative per cu.m.